Anya . Mother - Gimes, Miklós (Hungary, 2002)
Duration: 01:36:00 Portrait of Alice Gimes, Lucy, the filmmaker's mother. Raised in a comfortable assimilated Jewish home in southern Hungary, Lucy escaped being deported to Auschwitz and later committed herself to the communist movement. It was there she met Miklos Gimes, a journalist who grew disenchanted with the communist government. After the Soviets invaded Hungary in 1956, Miklos sent his wife and six-year-old son abroad. While in Vienna, Alice learned that her husband had been executed; eventually, she and her son settled in Switzerland. After the fall of communism, Miklos Gimes was to be given an official burial as a national hero - Lucy however hesitated to become the "official widow." This is the point of departure for the director who undergoes the painful exploration of his parents' personal relationship while creating an insightful meditation on the legacy of their politics for his own life.